Development of novel ultra-high performance concrete: From material to structure. (15th March 2017) - Su, Yu; Wu, Chengqing; Li, Jun; Li, Zhong-Xian; Li, Wengui
Highlights: Ultra-high performance concretes (UHPCs) were developed. Two best UHPC materials were selected to cast two beams for the static bending tests. One best UHPC material was selected to cast columns for the blast tests. Abstract: This paper investigates effects of nanoscale materials and steel fibres on properties of ultra-high performance concrete (UHPC). Different types of steel fibres including twisted steel fibre (TF), waved steel fibre (WF), and micro steel fibre (MF) together with different kinds of nano materials including Nano-CaCO3, Nano-SiO2, Nano-TiO2 and Nano-Al2 O3 are studied in the present research. Material compressive stress–strain relationships, strain energy absorption, the flexural strength and fracture energy absorption of UHPC with different nanoscale materials and steel fibres were compared and discussed. Laboratory static bending tests and field blast tests on structural components made of selected UHPC material composition were carried out, and the results highlighted the superior material ductility and blast resistant capacity of UHPC material developed in the present study.